Development of Young Varying Lemmings (Dicrostonyx) - Hansen, Richard M. (ARCTIC, 1957)
An outline of growth and development of Dicrostonyx groenlandicus rubricatus from birth till the age of 40 days. Appearance of hair and teeth, motion, development of sense organs, weaning, appearance of defensive behavior and of sexual maturity are traced, and weight increase recorded. Observations were made on a laboratory colony established from specimens captured at Umiat, Alaska.